2018
DOI: 10.1186/s12889-018-5737-6
|View full text |Cite
|
Sign up to set email alerts
|

Statewide dissemination and implementation of physical activity standards in afterschool programs: two-year results

Abstract: BackgroundIn 2015, YMCA afterschool programs (ASPs) across South Carolina, USA pledged to achieve the YMCA physical activity standard calling for all children to accumulate 30 min of moderate-to-vigorous physical activity (MVPA) while attending their ASPs. This study presents the final two-year outcomes from the dissemination and implementation efforts associated with achieving this MVPA standard.MethodsTwenty ASPs were sampled from all South Carolina YMCA-operated ASPs (N = 97) and visited at baseline (2015) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Cohen 2015 [27] Sutherland 2017 [28] How much of the intervention was provided? Beets 2018 [30] How much support to implement the intervention was provided? How much support to implement the intervention was provided?…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Cohen 2015 [27] Sutherland 2017 [28] How much of the intervention was provided? Beets 2018 [30] How much support to implement the intervention was provided? How much support to implement the intervention was provided?…”
Section: Studymentioning
confidence: 99%
“…In Table 1, we present examples from a sample of six interventions [25][26][27][28][29][30][32][33][34][35][36][37] related to childhood obesity that have a published efficacy and a subsequent effectiveness trial and one intervention [31] with only an efficacy evaluation published. In these studies [25][26][27][28][29][30][31][32][33][34][35][36][37], the authors indicate the substantially reduced or null effects observed in the effectiveness trial may be due to a feature of the efficacy study, such as delivery of the intervention by study personnel, being removed in the effectiveness trial [38]. These are but a few of the adaptations interventionists could make [39] that may lead to possible biases that distort the estimated impact of an intervention, especially during pilot testing.…”
Section: Rationale Of the Proposed "Risk Of Generalizability Biases"mentioning
confidence: 99%
“…The 14 included studies [17,149,156,[182][183][184][185][186][187][188][189][190][191][192][193] were conducted in only two countries, with the majority taking place in United States and the one other study conducted in Australia. The total sample size for all studies combined was 12,021 children (range 82 to 2,053, mean age = 8.3 years).…”
Section: Afterschool Programsmentioning
confidence: 99%
“…Five studies had more than 600 children [17,[182][183][184][185]. Cross-sectional studies represented the most common design [17,156,183,184,[186][187][188][189][190][191][192], and Actigraph was the only accelerometer brand used to measure PA and ST. The majority of the studies addressed the outcomes during afterschool hours only, while one considered all waking hours in addition to activity and sedentary during afterschool hours.…”
Section: Afterschool Programsmentioning
confidence: 99%
See 1 more Smart Citation